2009
DOI: 10.1556/aphysiol.96.2009.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of glutathione peroxidase activity in rat organs after lead exposure

Abstract: The activity response of the antioxidant enzymes glutathione peroxidase (GPx), glutathione reductase (GR) and the contents of thiobarbituric reactive substances (TBARS) were investigated in rats exposed to lead. The enzyme activities were determined in the liver, kidney and heart of male and female rats which were received 100 mg and 1000 mg of lead acetate per liter water for 18 weeks. The statistical analyses indicated the differences related to the organs and to the sex of animals. Administration of lead ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Some studies suggested that oxidative stress is a potential contributor to lead toxicity and that lead directly or indirectly changes the pro-oxidant and antioxidant balance in the biological system by the generation of more reactive oxygen species (ROS), which elicits oxidative damage of proteins, lipids and DNA [ 8 10 ]. Antioxidant defenses, such as catalase (CAT), superoxide dismutase (SOD) and glutathione reductase (GR), are involved in counteracting the toxicity of ROS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that oxidative stress is a potential contributor to lead toxicity and that lead directly or indirectly changes the pro-oxidant and antioxidant balance in the biological system by the generation of more reactive oxygen species (ROS), which elicits oxidative damage of proteins, lipids and DNA [ 8 10 ]. Antioxidant defenses, such as catalase (CAT), superoxide dismutase (SOD) and glutathione reductase (GR), are involved in counteracting the toxicity of ROS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, this decline may be due to the exhaustion and overutilization of these enzymes by the OS products. The differences in GPx activity observed in experimental studies can be attributed to differences in the animal species used or to the fact that some studies analyzed GPx in the erythrocytes (Sivaprasad et al 2003 ;Martinez-Haro et al 2011 ), while other studies examined the activity of GPx in renal and aortic tissues (Farmand et al 2005 ;Sobeková et al 2009 ). The different doses of lead used in these studies represent another possibility that explains the divergent outcomes (Farmand et al 2005 ).…”
mentioning
confidence: 99%
“…However, Kasperczyk et al ( 2009 ) reported a negative correlation between GPx activity and BLL. The differences in GPx activity observed in experimental studies can be attributed to differences in the animal species used or to the fact that some studies analyzed GPx in the erythrocytes (Sivaprasad et al 2003 ;Martinez-Haro et al 2011 ), while other studies examined the activity of GPx in renal and aortic tissues (Farmand et al 2005 ;Sobeková et al 2009 ). Sugawara et al ( 1991 ) also noted reduction in GPx activity in the case group and suggested that this decrease may play an important role in the enhancement of LPO.…”
Section: Lead Assessmentmentioning
confidence: 99%